Math, asked by as5538746, 4 months ago

p+q =√13, p-q=√13. find pq
plz explain simple way it's important​

Answers

Answered by Anonymous
6

Answer:

pq = 0

Step-by-step explanation:

Given:

  • p + q = √13
  • p - q = √13

To Find:

  • pq = ?

Solution:

We know that,

(p + q)² = (p - q)² + 4pq

=> (√13)² = (√13)² + 4pq

=> 13 = 13 + 4pq

=> 4pq = 13 - 13

=> 4pq = 0

=> pq = 0/4

pq = 0

Answered by sanjeevipfiles
0

pq = 0

Step-by-step explanation:

p+q = √13

p-q = √13

2p = 213

p=13.

substitute p = 13 in p+q =13

13+q = 13

q=0

Therefore, p*q = 13*0

p*q =0

Similar questions